2020
DOI: 10.1002/aoc.5957
|View full text |Cite
|
Sign up to set email alerts
|

Permethylated dinuclear Mn(III) coordination nanostructure with stripe‐ordered magnetic domains

Abstract: A di‐manganese(III) complex structure was built by an original approach consisting of a two‐step procedure. First, the mononuclear complex of the manganese(III) with the Schiff base of the salen‐type ligand (H2L) derived from 1,3‐bis(3‐aminopropyl)tetramethyldisiloxane and 3,5‐di‐tert‐butyl‐2‐hydroxybenzaldehyde was prepared. The main feature of note is the 12‐membered chelate ring formed upon coordination of the Schiff base to central atom, which adopts a distorted N2O4 octahedron environment. In the second s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Thermally induced switching to a different spin state in Mn 3+ can therefore be expected to profoundly affect the magnitude and possibly also the sign of D . Identification of the sign of D is particularly relevant to the current work because, although the majority of known (HS) Mn 3+ complexes display a pronounced axial elongation due to the Jahn–Teller effect, most Mn 3+ SCO complexes appear to have a marked compression in the spin quintet form. ,,,,,, An axially compressed form may assist the transition to a spin triplet arrangement as the energetic order of orbitals should match that expected in the S = 1 form of the ion (Figure ). Diffraction alone, however, is not sufficient to discern if this is a genuine compression, but it can be resolved by measuring the sign of D by EPR at high fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermally induced switching to a different spin state in Mn 3+ can therefore be expected to profoundly affect the magnitude and possibly also the sign of D . Identification of the sign of D is particularly relevant to the current work because, although the majority of known (HS) Mn 3+ complexes display a pronounced axial elongation due to the Jahn–Teller effect, most Mn 3+ SCO complexes appear to have a marked compression in the spin quintet form. ,,,,,, An axially compressed form may assist the transition to a spin triplet arrangement as the energetic order of orbitals should match that expected in the S = 1 form of the ion (Figure ). Diffraction alone, however, is not sufficient to discern if this is a genuine compression, but it can be resolved by measuring the sign of D by EPR at high fields.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Mn 3+ , which is also a non-Kramers ion and for which thermal SCO is now well-established, ,, switches between the fully unpaired spin quintet and partially paired spin triplet forms; therefore, a considerable ZFS is expected to persist at low temperature. Spin triplet Mn 3+ is generally not common, with about 20 examples at room temperature, , and the ZFS interactions have been quantified via the D and E parameters in just two cases. , These studies have however demonstrated that spin triplet Mn 3+ has the highest ZFS parameters for any manganese ion, with D values in the range +15 to +20 cm –1 , while the axially elongated spin quintet form shows small but negative values in the range of −4.5 to −1.2 cm –1 with only a small number of published spin quintet Mn 3+ examples with positive D values, i.e., axial compression of the Jahn–Teller ion. , In these examples, the sign and magnitude of the ZFS parameters have been examined in selected examples by Tregenna-Piggott, , Krzystek and Telser, , and Duboc and Neese, ,,, who have built on the earlier studies of Gregson in probing the electronic structure . Thermally induced switching to a different spin state in Mn 3+ can therefore be expected to profoundly affect the magnitude and possibly also the sign of D .…”
Section: Introductionmentioning
confidence: 99%
“…With structures built around nitrogen atoms and ease of synthesis, the Schiff bases are desirable chelating agents [ 29 ]. The ease of synthesis allows the tuning of the properties of interest of the Schiff bases for targeted applications in biomimetic chemistry [ 30 ], analytical chemistry [ 31 ], materials chemistry [ 32 ], and catalysis [ 33 , 34 , 35 , 36 ], with efficient catalysis of click reaction in aqueous media [ 37 ], cyclic carbonates [ 38 ], spin crossover complexes and materials for magnetic recording [ 39 , 40 , 41 ], and single crystal materials with large dielectric constant [ 42 ]. The ability of Schiff bases to coordinate the metal within the polymer-based macromolecules provides the functionality required for sensors and actuators [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Mn–O/N bond lengths of Mn1 center of 1 clearly suggest that Mn1 with O 6 donor set center has undergone a JT tetragonal compression (Mn–O axial 1.867/1.864 Å; Mn–O equatorial 2.182, 2.021, 1.993, 2.139 Å) while the Mn2 center with a N 2 O 4 donor set possesses a JT Mn–N bond elongation (Mn–N axial 2.323/2.347 Å; Mn–O equatorial 1.881, 1.881, 1.967, 1.948 Å) (Table ). ,, This structural feature is unprecedented in the literature, although there have been reports of a plethora of Mn and Mn–Ni complexes to date.…”
Section: Introductionmentioning
confidence: 99%
“…The Mn III ion may undergo either JT elongation or JT compression of the axial bond lengths, which has significant and captivating effects on its spin relaxation at low temperatures. The occurrence of the former phenomenon is quite frequent due to the population of d z 2 orbital, while the number of the latter contains only a handful of examples in Mn III complexes. It has been established by spectroscopic, magnetic studies, and theoretical calculations that Mn III ions having tetragonal JT elongation contribute negative D (zero-field splitting; zfs) while Mn III ions with JT axial compression possess positive D , which is remarkable from the point of view of molecular magnetism ,, having a significant implication on the physical properties of complexes containing Mn III ions. SMM behavior of Mn III -containing complexes largely depends on the negative D value of Mn III ions .…”
Section: Introductionmentioning
confidence: 99%